GAMBARAN TINGKAT PENGETAHUAN KESEHATAN GIGI DAN MULUT DI RW 15 PERUM BAROS KENCANA KOTA SUKABUMI (Politeknik Kesehatan Kemenkes Bandung, 2021)
Dental and oral health efforts are assessed from several aspects, one of which is knowledge obtained from the educational process. A person's knowledge will determine his behavior in terms of health. The purpose of this study is to determine the level of knowledge of oral health in RW 15 Perum Baros Kencana Sukabumi City and to know the level of knowledge of dental and oral health based on the level of education. This research method is a descriptive study using a frequency distribution table. The population of this study was 43 people. Sampling was done by filling out google forms and analysis using cross tabulation. the results show that the level of knowledge of adolescents about dental and oral health is included in the sufficient category (51.2%), then based on the level of education at the junior high school level is included in the sufficient category of 6.9%, high school is included in the sufficient category of 14 .2%, and tertiary institutions are included in the sufficient category of 30.9%. The level of knowledge of adolescents about oral health based on the level of education shows that the higher the education, the higher the knowledge of oral health.